Pendidikan Terbelah: Telaah Posisi Perguruan Tinggi Keagamaan Islam Dalam Sistem Pendidikan Nasional - Moch Iqbal (Institut Agama Islam Negeri Bengkulu, 2020)
Abstract: Divided Education: Analyzing the Position of Islamic Religious Colleges in the National Education SystemThe purpose of this paper is to examine the higher education system in Indonesia and its implications for its scientific characteristics. Using library research (literature study), which is how to collect data and information from books and scientific journals related to research objects that are discussed descriptively-analytically through philosophical studies with a qualitative-rationalistic approach. The results of the study of this paper show that first, the dichotomy between science and religion which is then followed institutionally is the remnants of Dutch colonial politics. Where it was deemed incompatible with the science developed in Dutch schools. Second, Islamic educational institutions, especially Islamic boarding schools, which were originally places for religious learning and a means of resistance to colonialism, experienced institutionalization and continued to distance themselves from science and technology studies. Islamic education is more dominant as conservation of schools and beliefs than as a center for scientific and technological studiesAbstrak: Pendidikan Terbelah: Telaah Posisi Perguruan Tinggi Keagamaan Islam Dalam Sistem Pendidikan NasionalTujuan dari penulisan ini adalah mengkaji sistem pendidikan tinggi di Indonesia dan implikasinya terhadap karakteristik keilmuannya. Menggunakan library research (studi pustaka), yaitu cara mengumpulkan data-data dan informasi dari buku-buku serta jurnal-jurnal ilmiah yang terkait dengan objek penelitian yang dibahas secara deskriptif-analitik melalui kajian secara filosofis dengan pendekatan kualitatif-rasionalitik. Hasil kajian paper ini menunjukkan bahwa pertama, dikotomi antara sain dan agama yang kemudian diikuti dengan secara kelembagaan, adalah sisa-sisa politik pecah belah kolonial Belanda. Di mana dianggap tidak sesuai dengan ilmu pengetahuan yang dikembangkan di sekolah-sekolah Belanda Kedua, lembaga pendidikan Islam terutama pesantren yang semula sebagai tempat belajar agama dan alat perlawanan terhadap kolonial, mengalami institusionalisasi dan terus menjaga jarak dengan kajian sains dan teknologi. Pendidikan Islam lebih dominan sebagai konservasi mazhab dan keyakinan dari pada sebagai pusat kajian keilmuan dan teknologi.